The Rationale and Design of Inflation-Indexed Bonds - Price, Robert (IMF Working Papers; Working Paper, 1997)
A number of industrialized countries have recently offered inflation-indexed bonds. Some members of another group of countries that had earlier adopted more comprehensive indexation in response to high inflation have taken steps to reduce the scope of indexation in their economies. This paper surveys debt management, monetary policy, and welfare arguments on the use of inflation-indexed bonds, and relates these to the experiences of various issuers. The paper also considers some important design features of indexed bonds.